Cure acceleration and plasticizing effect of imidazolium ionic liquid on the properties of natural rubber/carbon nanotube composites. (4th September 2020) - Therattil, JessyAnto; Anil, Kumar S; Pothan, Laly A; Rouxel, Didier; Maria, Hanna J; Kalarikal, Nandakumar; Thomas, Sabu
Abstract: Natural rubber (NR)/carbon nanotube (CNT) composites containing ionic liquid (IL) at different concentrations have been prepared by using an internal mixer in the conventional mechanical mixing method. The role of a green solvent IL 1-butyl-3-methyl imidazolium chloride (BMIC) on the curing kinetics, mechanical, morphological and thermal properties of NR–CNT composites has been studied. It has been found that BMIC strongly influenced rheometric data and mechanical properties. The addition of the IL (1-ethyl-3-mehylimidazolium chloride) significantly increased the vulcanization rate, decreased scorch and cure times. The plasticizing effect of IL on the composite is well understood from the results of different analysis. The increment in the free volume of the nanocomposites by the effect of IL was studied using positron annihilation lifetime spectroscopy. The mechanical properties such as tensile strength and elongation at break increased with small amount of IL. With high amount of IL, tensile strength and elongation at break decreased due to plasticizing effects, contributing towards retarding the strain-induced crystallization in NR/CNT/IL composites. Differential scanning calorimetry analysis was done and the improvement in dispersion of the CNTs by the addition of IL has been investigated through transmission electron microscopy analysis.